LEARNERS PERCEPTIONS ON THE USE OF INDONESIAN (L1) IN THE ENGLISH (L2) INTENSIVE COURSE: IMPLICATIONS FOR TRANSLANGUAGING PEDAGOGY - Puspitasari, Gregoria Dian; Yumarnamto, Mateus (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2020)
This study explores the use of Indonesian (L1) in an English class at an undergraduate program in a university in East Java, Indonesia. The English class was called Intensive Course (IC). In the class the students were expected to learn general English so that they could have the required competence to become English teachers. The students who passed the course in 2018-2019 (50 students) were asked to complete a questionnaire. Follow up interviews were conducted to four selected students representing positive and negative perceptions on the use of Indonesian. The findings of this study shows that L1 could be a potential resource to learn English but when the L1 was overused in the classroom, the learning opportunities and exposure to the target language diminished, limiting their learning opportunities and bringing about negative perceptions of the students. Implications from the findings are discussed in relation to translanguaging as pedagogy.